STUDY OF DIURETIC ACTIVITY OF ETHONOLIC EXTRACT OF LEAVES OF CISSAMPELOS PAREIRA IN RATS - Sayana, Suresh Babu; Christina, Christina; Medabala, Tambi; Patil, Praveen S (Asian Journal of Pharmaceutical and Clinical Research, 2014)
ABSTRACT Objective: To study the diuretic activity of ethanolic extract of leaves of Cissampelos pareira (EELCP) by Lipschitz method in albino rats . Methods: Five groups of Albino rats were used to study the diuretic activity of EELCP by using metabolic cages. Group-I serves as normal control received vehicle (CMC 2% in normal saline), group II received Furosemide (10 mg/kg, p.o) in vehicle; other groups III, IV and V were treated with low (100 mg/kg), medium (200 mg/kg), and high (400 mg/kg) doses of EELCP in vehicle . Immediately after the extract treatment all the rats were hydrated with saline (15 ml/kg,p.o) and placed in the metabolic cages (3 per cage), specially designed to separate urine and faeces, kept at 21°C±0.5°C.The total volume of urine collected was measured at the end of 5th h. During this period, no food and water was made available to animals. Various parameters like total urine volume and concentration of Sodium, Potassium , Chloride ions in the urine were measured and estimated respectively. Results: When compared to vehicle treated control group the EELCP at different dose levels (100,200 and 400 mg/kg) has significantly increased the urine volume and also enhanced the elimination of Sodium, Potassium and Chloride ions in urine. Conclusion : Results showed that single dose administration of EELCP as 100, 200 and 400 mg/Kg and standard Furosemide (10 mg/kg b.wt) has significantly ( p<0.001***) increased the urine output along with an increase in concentration of Sodium, Potassium, and Chloride.